The Company’s Financial Structure Analysis - Dunakhir, Samirah (PINISI Discretion Review, 2025)
This study aims to analyze the financial structure of the Company. The financial structure shows how the company finances its assets. The company can fund its assets with short-term debt, long-term debt, or shareholders' equity. This study uses a quantitative approach. The population in this study is the Company listed on the Indonesia Stock Exchange (IDX). Sampling was carried out using the purposive sampling technique, which is a sampling technique with certain considerations and criteria with a sample of 14 companies. The data collection technique used is documentation. The data analysis technique uses descriptive analysis that describes the state of the Company's financial structure in more detail. The results of the study indicate that the Company's financial structure is very much influenced by its asset structure and capital structure. Thus, it is recommended that companies pay attention to the asset structure and capital structure of their companies because they are one of the sources of information used by interested parties from outside the Company and parties within the company itself.